2023
DOI: 10.5194/tc-17-3229-2023
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric highs drive asymmetric sea ice drift during lead opening from Point Barrow

Abstract: Abstract. Throughout winter, the winds of migrating weather systems drive the recurrent opening of sea ice leads from Alaska's northernmost headland, Point Barrow. As leads extend offshore into the Beaufort and Chukchi seas, they produce sea ice velocity discontinuities that are challenging to represent in models. We investigate how synoptic wind patterns form leads originating from Point Barrow and influence patterns of sea ice drift across the Pacific Arctic. We identify 135 leads from satellite thermal infr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Spatial discontinuities develop in the sea ice velocity field as lead patterns open, delineating portions of the pack that lose and remain in contact with the coast. Previous studies have suggested that coastal lead opening events in the Beaufort Sea play an important role in winter ice transport by temporarily enhancing rates of wind-driven ice drift as the ice separates from the coast (Lewis and Hutchings, 2019;Jewell et al, 2023). In agreement with these observational findings, model simulations of an exceptional coastal lead opening event in winter 2013 showed that the event enhanced MYI export from the Beaufort Sea (Rheinlaender et al, 2022).…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations
“…Spatial discontinuities develop in the sea ice velocity field as lead patterns open, delineating portions of the pack that lose and remain in contact with the coast. Previous studies have suggested that coastal lead opening events in the Beaufort Sea play an important role in winter ice transport by temporarily enhancing rates of wind-driven ice drift as the ice separates from the coast (Lewis and Hutchings, 2019;Jewell et al, 2023). In agreement with these observational findings, model simulations of an exceptional coastal lead opening event in winter 2013 showed that the event enhanced MYI export from the Beaufort Sea (Rheinlaender et al, 2022).…”
Section: Introductionmentioning
confidence: 55%
“…Several observational studies have identified changes in the rate and efficiency of winter sea ice transport in association with opening of leads in the Beaufort Sea (Lewis and Hutchings, 2019;Jewell et al, 2023). To evaluate change in ice motion, these studies often rely on satellite-derived sea ice drift products, which are typically available at daily temporal resolution.…”
Section: Spatiotemporal Patterns Of Sea Ice Motion During Event E5mentioning
confidence: 99%
See 2 more Smart Citations
“…In the late winter and spring, the Beaufort has high sea ice concentration. As external stresses, such as wind stress, are applied to the ice pack, the ice pack experiences strain, leading to fracture in a preferential direction that depend on the force's orientation relative to the coast (Lewis and Hutchings, 2019;Jewell et al, 2023). When we examine the newly fractured floes during this time period, we find a low variability in their orientation (Fig.…”
Section: Floe Orientationmentioning
confidence: 90%